Assessing the Comprehensiveness of Supply Chain Environmental Strategies. (13th September 2012) - Comas Martí, Joana M.; Seifert, Ralf W.
ABSTRACT As environmental awareness grows, firms are expected to expand the scope of their environmental strategies beyond organisational boundaries and to address more comprehensively environmental issues in their supply chains and product life cycles. Drawing on different literature streams, international standards and corporate disclosure, this paper presents a conceptual framework for the quantitative assessment of the comprehensiveness of firms' environmental strategies. This framework allows us to capture: (i) the environmental inputs and outputs addressed, (ii) the firm versus supply chain orientation of environmental strategies, and (iii) the environmental management practices adopted by companies. We illustrate the application of this framework with a content analysis of corporate sustainability reports for a cross‐sectoral sample of sustainability leaders. Our results indicate that there is a need for greater specificity in environmental reporting and that, overall, companies remain firm‐oriented. It is also observed that supply chain orientation can generally be associated with stakeholder pressure. Copyright © 2012 John Wiley & Sons, Ltd and ERP Environment.